Representations of solutions of nonlocal boundary-value problems for parabolic equations - Korbut, L. I.; Matychuk, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study two-point boundary-value problems for parabolic equations whose solutions are representable in terms of Green’s functions of the Cauchy problem.